GOVERNING EUROPEAN UNION TO FINANCIAL STABILITY - Ion-Lucian CATRINA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
In the last four years, a significant part of the European Union members has recorded a real decline in the sustainability of their public debt. The failure of Greece, Italy, Belgium or Spain to easily find funding at previous interest rates has induced the fear that the European Monetary Union would disintegrate. Such as scenario is not realistic because does not take into account the economic interdependencies that have been created between the countries participating at the monetary zone. Nevertheless, we can say that the Stability and Growth Pact which aimed towards the coordination of national fiscal policies for ensuring the stability and prudence of the budgetary climate, has failed. This failure was primarily due to the lack of specific sanctions for those members that have not fought against the fiscal imbalances and secondly to the stopping the steps forward towards a common fiscal policy. Thus, we can say that the European Monetary Union is driven now by the wrong rule of “no taxation with representation”. For these reasons, this paper aims at showing that the European fiscal federalism is still far away from becoming reality and that the new instruments chosen for the new stability of the European Monetary Union will be the task of the Member States themselves. This paper will also review the main rules that are projected to be the source for the future European financial stability and growth: the balanced budgets and the deficits built only on the “Golden Rule” premises, for which other amendments on European Treaties are expected.